Ahl as Sunnah waal Jama - Anwar, Khairil (NALAR, 2022)
This study focused on the early history of the emergence of the ahl as-sunnah waal-jamāʻah (Sunnism) and its development in Indonesia. This study also compared al-Banjari's Sunnism with Indonesia's Islamic group Nahdlatul Ulama